The Relationship Of The Management Of Effective Sentences With Writing Skills Of Class X Students Of Willem Iskander Vocational School - Masridah Masridah (Indonesian Journal of Education and Mathematical Science, 2020)
Good writing skills are obtained by repeated practice and it takes a long time, considering that writing is very complex in the sense that it involves various skills to express ideas, thoughts, knowledge, and life experiences in clear, coherent, expressive written language. , and easy to understand. In writing learning activities, students are directed to be able to express their ideas coherently with the right diction, the correct structure according to the context. The purpose of this study was to increase the mastery of effective sentences on the skills of writing arguments and to determine the learning achievement of class X students of SMK Willem Iskandar. This research is descriptive quantitative, from the results of the research, the average value of the students' ability of KLS X in Willm Iskandar Vocational High School in writing argumentation discourse in terms of the equivalence and coherence aspects of argumentation sentences is 11.22%, the parallel aspect of argumentation sentences is 11.74% , the aspect of the assertiveness of the argumentation sentence was 13.45%, the aspect of the accuracy of the argumentation sentence was 12.06%, the aspect of the plausibility of the argumentation sentence was 13.86%. Meanwhile, the ability level of Kls X Vocational High School Willem Iskandar students in writing argumentation discourse using the sentence mastery aspect was 76.22% and it was categorized as good.